HUBUNGAN PENGETAHUAN IBU TENTANG PERSIAPAN LAKTASI PADA TRIMESTER III DENGAN KELANCARAM ASI PADA IBU NIFAS - Lina Windasari; Lutvia Dwi Rofika; Endah Kusuma Wardani (Ensiklopedia Research and Community Service Review, 2026)
Background: Exclusive breastfeeding at the age of 0-6 months globally and nationally is not yet optimal, this is because at the beginning of the postpartum period many people are faced with irregular milk production. The mother's knowledge about lactation management since pregnancy will influence the smooth flow of breast milk during the postpartum period. This study aims to analyze the relationship between maternal knowledge about lactation preparation in the third trimester and smooth breastfeeding in postpartum mothers. Method: This type of research is quantitative, analytical observational research design with a cross sectional approach. The total sample was 33 people determined using accidental sampling technique. This research was carried out at TPMB Siti Rubiyanti on 12 December 2023 – 20 January 2024. Data analysis used the Spearman Rank correlation test. Results: The results of the study showed that the majority of respondents with less knowledge about lactation preparation in the third trimester were 20 postpartum mothers (60.6%), and almost all postpartum mothers' breast milk was not smooth, 27 people (81.8%). The results of the analysis using the Spearman Rank correlation test showed a value of p = 0.002 α 0.05, meaning that there is a relationship between maternal knowledge about lactation management in the third trimester and smooth breastfeeding in postpartum mothers. Conclusion: The results of this study can be used as a reference to increase knowledge to pregnant women third trimester by providing counseling/KIE obiut purpose lactation management during pregnancy.Keywords: Smooth breastfeeding, knowledge, lactation management